2020
DOI: 10.1590/1518-8345.3467.3378
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the rapid triage conducted by nurses at the emergency entrance

Abstract: Objective: to compare the performance of the rapid triage conducted by nurses at the emergency entrance and of the Manchester Triage System (MTS) in identifying the priority level of care for patients with spontaneous demand and predicting variables related to hospitalization. Method: a cross-sectional study carried out in an Emergency Department (ED) of a university hospital in São Paulo. The priority levels established in the rapid triage performed by nurses were high priority (patients of spontaneous deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Previous studies on EDs in general hospitals revealed that there was poor agreement in triage between nurses and physicians, and nurses had a tendency to assign patients higher triage grades than physicians ( 10 , 11 ), yet there was reasonably substantial agreement between the two groups in our records. There were two explanations for the distinction.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Previous studies on EDs in general hospitals revealed that there was poor agreement in triage between nurses and physicians, and nurses had a tendency to assign patients higher triage grades than physicians ( 10 , 11 ), yet there was reasonably substantial agreement between the two groups in our records. There were two explanations for the distinction.…”
Section: Discussionmentioning
confidence: 49%
“…Historically, registered nurses have been the first line to perform triage in many countries’ EDs ( 6 ). Previous studies have found that nurses in general EDs tend to assign patients to more urgent categories to avoid missing critical patients ( 10 , 11 ). However, there are currently little data in the literature on nurses’ prioritization preference for ophthalmic emergencies.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies point out that some patients, mainly elderly people, women and diabetics, require greater attention at the time of care, as they may present atypical clinical symptoms of coronary diseases more frequently, with diagnosis and management being directed, initially, for other diseases and comorbidities (10,14,24) .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that there are different classification protocols, and some of them allow more subjectivity in the evaluation than others, even if evaluators follow the same parameters to determine the severity and priority of care (10,11) .…”
Section: Introductionmentioning
confidence: 99%
“…Based on rapid screening models commonly used in the prehospital setting, for example, the triage sieve, where the primary assessment identifies the victim's ability to walk, breathing and pulse (Smith, 2012), the ‘quick look nurse’ (Lauks et al, 2016), and in the effect of direct communication between triage nurse and emergency physician on reducing patient door‐to‐doctor and initial assessment time (Rahmatullah et al, 2017), this study's object will call the nurse's rapid assessment ‘rapid triage’. In other terms, rapid triage is a quick look from the nurse of an emergency patient's presentations when arriving at an emergency department (ED) with severe complaints reported by themselves or their companions (Moura & Nogueira, 2020).…”
Section: Introductionmentioning
confidence: 99%